2004
DOI: 10.1021/jp047330g
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of 13C-Iodomethane:  Different Behavior in Thermotropic and Lyotropic Liquid Crystals

Abstract: High-resolution NMR spectra of 13C-iodomethane dissolved in thermotropic and lyotropic liquid crystalline solvents have been used to measure 1H−H and 13C−1H dipolar couplings. The ratio of these two couplings, which is a function of the H−C−H bond angle in 13C-iodomethane, is, in general, different from that expected from the known molecular structure; solvent−solute interactions in liquid crystalline solutions are responsible for this difference. In thermotropic liquid crystalline solutions, the apparent bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Indeed, only small variations in RDCs were observed earlier in these weakly aligning SDS-based systems, compared to large deviations in thermotropic liquid crystals. 10,30,40 However, unusual behavior was also observed by other groups in strongly aligned lyotropic systems when high concentrations of SDS and low concentrations of alcohol were employed. 42,43 Although SDS-based systems are not wide-spread systems for aligning biomolecules, SDS is frequently used as an additional component in other media, either as a stabilizing agent, 44,45 a compound for modulating the tensor orientation of the biomolecule or for altering the charge of a micelle.…”
Section: Anionic Surfactants Based On Sodium Dodecyl Sulfatementioning
confidence: 66%
See 3 more Smart Citations
“…Indeed, only small variations in RDCs were observed earlier in these weakly aligning SDS-based systems, compared to large deviations in thermotropic liquid crystals. 10,30,40 However, unusual behavior was also observed by other groups in strongly aligned lyotropic systems when high concentrations of SDS and low concentrations of alcohol were employed. 42,43 Although SDS-based systems are not wide-spread systems for aligning biomolecules, SDS is frequently used as an additional component in other media, either as a stabilizing agent, 44,45 a compound for modulating the tensor orientation of the biomolecule or for altering the charge of a micelle.…”
Section: Anionic Surfactants Based On Sodium Dodecyl Sulfatementioning
confidence: 66%
“…Moreover, we previously showed that solute structural parameters determined in thermotropic liquid crystals exhibited the largest deviations for the most weakly aligned molecules. 30 We also noted a correlation between the apparent structural deviations and the physical characteristics of the thermotropic liquid crystals, such as dielectric and diamagnetic anisotropies.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Comparisons of these two methods, and also with structures obtained from rotational spectroscopy, are usually within much closer agreement. 20 There are cases, however, involving small molecules, such as methyl fluoride 21 and methyl iodide, 22 when very large, and temperature-and solvent-dependent discrepancies are observed. These cases are most probably because of multiple site-specific interactions between the solute and solvent molecules.…”
Section: Discussionmentioning
confidence: 99%